2008
DOI: 10.1051/medsci/20082410821
|View full text |Cite
|
Sign up to set email alerts
|

Survivine en cancérologie

Abstract: Découverte il y a 10 ans [1], Survivine a rapidement attiré l'attention de la communauté scientifique par sa biologie fascinante et son potentiel thérapeutique en cancérologie. Conservée au cours de l'évolution, Survivine appartient à la famille des IAP (inhibitors of apoptosis proteins), définie par le domaine structurel BIR caractérisé à l'origine chez le baculovirus pour son rôle dans la protection vis-à-vis de l'apoptose. Chez les mammifères, Survivine fut initialement décrite comme importante pour la surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…COX-2 and survivin promote the survival of tumor cells [13-15]. Studies also showed that COX-2 is closely associated with survivin [16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 and survivin promote the survival of tumor cells [13-15]. Studies also showed that COX-2 is closely associated with survivin [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to unique structure of survivin, it is considered a potent target for chemo- and radiotherapy of cancer [13,26,27]. In KBM-5 cells, it was recently reported that targeting survivin could overcome the resistance against imatinib, a bcr-abl inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of survivin is strictly controlled in embryonic tissues and in the majority of tumors, but not during tissue differentiation and maturation ( 23 , 24 ). Thus, survivin presents an attractive target for cancer therapy ( 25 ), and has been extensively studied in cell cycle and apoptotic assays for cancer cells ( 26 , 27 ). Studies have demonstrated that the oncofetal gene, survivin, is re-expressed in osteoarthritis and rheumatoid arthritis ( 28 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the mechanisms underlying disc degeneration, including a decrease in cellular concentration, cell senescence, cell apoptosis, decreasing extracellular matrix anabolism and increasing extracellular matrix catabolism ( 27 , 28 ). The role of oncofetal gene survivin has been extensively investigated in cell proliferation and apoptosis in tumor cells ( 29 , 30 ). However, limited data is available regarding its expression in degenerative NP cells.…”
Section: Discussionmentioning
confidence: 99%